Relevansi Penerapan Asas Oportunitas Dalam Sistem Peradilan Pidana Indonesia Dihubungkan Dengan Asas Persamaan Kedudukan Di Hadapan Hukum; The Relevance Implementation of the Opportunity Principle in the Indonesian Criminal Justice System Related to the Equality before the Law Principle - Kharisma Ramadhan (Faculty of Law, Universitas Padjadjaran, 2018)
AbstractIn the Indonesian criminal justice system, dismissal of cases for the good of public interest is a manifestation of the principle of opportunity as set forth in Article 35(c) of Law Number 16 of 2004 on Indonesian Attorney. The application of the principle of opportunity is deemed to contradict the principle of equality before the law, which is introduced in the Indonesian Constitution, because it creates discrimination in the process of law enforcement. The absence of a comprehensive legislation policy on the application of the principle of opportunity in the Indonesian criminal justice system has led to contradictions. It weakens the principle of equality before the law, which has been guaranteed by the constitution. In addition, it can cause constitutional harm to a number of citizens. Nevertheless, the existence of the principle of opportunity remains recognized in the Indonesian criminal justice system because, in principle, it contains the values of goodness to balance the sharp principles of legality. This writing aims to analyze and to understand the legislation policy on the application of the principle of opportunity. It also reveals the meaning of abstraction and multiple interpretations of public interest, the influence of the application of the principle of opportunity to the principle of equality before the law, and the relevance of the application of the principle of equality and the principle of equality before the law.AbstrakDalam sistem peradilan pidana Indonesia, pengesampingan perkara demi kepentingan umum merupakan perwujudan dari asas oportunitas yang dituangkan dalam ketentuan pasal 35(c) UU No. 16 Tahun 2004 Tentang Kejaksaan RI. Penerapan asas oportunitas tersebut dianggap bertentangan dengan asas persamaan kedudukan di hadapan hukum yang telah diintrodusir dalam Konstitusi negara Indonesia karena menimbulkan diskriminasi dalam proses penegakan hukum. Tidak adanya kebijakan legislasi yang komprehensif tentang penerapan asas oportunitas dalam sistem peradilan pidana Indonesia menyebabkan pertentangan yang justru melemahkan asas persamaan kedudukan di hadapan hukum yang telah dijamin oleh konstitusi dan dapat menyebabkan kerugian konstitusional terhadap sebagiian warga negara. Meskipun demikian keberadaan asas oportunitas tetap diakui dalam sistem peradilan pidana Indonesia, karena pada prinsipnya mengandung nilai-nilai kebaikan untuk mengimbangi tajamnya asas legalitas. Penulisan ini bertujuan untuk menganalisis dan memahami tentang kebijakan legislasi penerapan asas oportunitas juga terkait makna kepentingan umum yang bersifat abtrak dan multitafsir, pengaruh penerapan asas oportunitas terhadap asas persamaan kedudukan di hadapan hukum, serta relevansi penerapan asas oportunitas dengan asas persamaan kedudukan di hadapan hukum. DOI: https://doi.org/10.22304/pjih.v5n2.a4